Association of citrulline concentration at birth with lower respiratory tract infection in infancy: Findings from a multi-site birth cohort study - Snyder, Brittney M.; Gebretsadik, Tebeb; Turi, Kedir N.; McKennan, Christopher; Havstad, Suzanne; Jackson, Daniel J.; Ober, Carole; Lynch, Susan; McCauley, Kathryn; Seroogy, Christine M.; Zoratti, Edward M.; Khurana Hershey, Gurjit K.; et al. (Frontiers in Pediatrics, 2022)
Assessing the association of the newborn metabolic state with severity of subsequent respiratory tract infection may provide important insights on infection pathogenesis. In this multi-site birth cohort study, we identified newborn metabolites associated with lower respiratory tract infection (LRTI) in the first year of life in a discovery cohort and assessed for replication in two independent cohorts. Increased citrulline concentration was associated with decreased odds of LRTI (discovery cohort: aOR 0.83 [95% CI 0.70-0.99], p=0.04; replication cohorts: aOR 0.58 [95% CI 0.28-1.22], p=0.15). While our findings require further replication and investigation of mechanisms of action, they identify a novel target for LRTI prevention and treatment.